A business ecosystem perspective of supply chain justice practices: A study of a marina resort supply chain ecosystem in Indonesia. Issue 9 (25th September 2019) - Liu, Gordon; Aroean, Lukman; Ko, Wai Wai
Abstract : Purpose: The purpose of this paper is to investigate the influence of supply chain (SC) justice practices in shared value-supplier delivery performance relationship and the contingent role of trust in SC ecosystem operation. Design/methodology/approach: The authors collect and analyze dyadic survey data from a marina resort SC ecosystem in Indonesia. Findings: The results suggest the differential moderating effects of two types of perceived SC justice – perceived procedural justice and perceived interactional justice – on the relationship between shared value and supplier delivery performance. More specifically, we find that perceived procedural justice strengthens the shared value-supplier delivery performance relationship, but that perceived interactional justice weakens such a relationship. Furthermore, the findings demonstrate a positive three-way interaction effect between shared value, perceived SC justice and trust on supplier delivery performance. Originality/value: The study is the first to introduce the role of SC justice practices in SC ecosystem operation. The authors examine how shared value interacts with perceived SC justice and trust in order to determine supplier delivery performance.